Selective-Delay Garbage Collection Mechanism for Read Operations in Multichannel Flash-Based Storage Devices - Paik, Joon Young; Cho, Eun Sun; Jin, Rize; Chung, Tae Sun (IEEE Transactions on Consumer Electronics, 2018)
Flash memory has been a dominant storage medium in consumer electronics. Its wide deployment results from the remarkable progress in garbage collection mechanism which resolves the inherent limitation, not-in-place-update property, of flash memory. In this paper, we propose a new garbage collection management scheme, called selective-delay garbage collection, which can be used to optimize read operations. In our proposal, garbage collections are allowed to proceed only if they do not block the execution of incoming read operations. For this, the proposed scheme cooperates with an event queue in storage devices of consumer electronics. When read operations in the event queue are likely to collide with a garbage collection request, the read operations are processed preferentially by delaying garbage collection. This reduces the average read latency by avoiding time-consuming garbage collections. The experimental results with realistic workloads show that average read latency decreases by up to 13.53%, and the time elapsed by garbage collections is reduced by up to 78.37%, whereas the increase in write latency is limited to 0.83%.
Keywords: Garbage collection; In-place update; Inherent limitations; Multichannel; Read latencies; Read operation; Storage medium; system performance; Consumer electronics; flash memory; garbage collection; semiconductor devices; system performance